Utilization of cockle shell powder as an adsorbent to remove phosphorus-containing wastewater - Nayeem, Abdullah; Farahin, Mizi; Mohd Faizal, Ali; Jun Haslinda, Shariffuddin (Elsevier Ltd, 2023)
The paper demonstrates the capability of using cockle shells as an adsorbent for phosphorus removal from simulated petrochemical wastewater, focusing on the actual condition of the petrochemical facultative pond. In this study, the physicochemical properties of shell powder were determined, such as the functional groups, surface morphology, crystalline structure, and surface area using FTIR, SEM, EDX, XRD, and BET. It was observed that the optimum conditions for effective phosphorus removal are under the presence of rotational speed (125rpm), higher dosage (7 g/L), and larger surface area (smaller particle size) of the shell powder. Fine powder achieved up to 52.27% of phosphorus removal after 40 min compared to coarse powder which could only give 16.67% removal. Additionally, calcined shell powder demonstrated a higher phosphorus removal rate, i.e., up to 62.37%, compared to raw shell powders. The adsorption isotherm was studied using Langmuir and Freundlich models, but the isothermal data fit better for the Freundlich model (R2 = 0.9836). Overall, this study has successfully generated a greener and low-cost adsorbent.